Tablet-Based Praxis Developed for Children in Primary Education Studying Natural Sciences and Mathematics - María-Carmen Ricoy; Cristina Sánchez-Martínez (MDPI AG, 2023)
Information and Communication Technologies are now a common feature in classroom activities. The aim of this study was to present praxis developed for the tablet for use by primary education students (aged 6-12) studying the natural sciences and mathematics. This research is qualitative and follows the narrative-ethnographic approach. The study sample consisted of 120 primary education students and 52 educational blogs. The results and conclusions reveal praxis that is rarely innovative or ludic. The bulk of tablet-based activities were for natural sciences classes rather than mathematics, and the most common practice with the tablet in the natural sciences was information searching and content exploration. The most widely used apps were the Google search engine, YouTube and the tablet's default apps (camera, image and video editor). Course content in the natural sciences focused on living beings and states of matter, and the activities developed for children to do on the tablet aimed to foster learning through discovery, exploration and enquiry. In mathematics, a traditional methodological approach was apparent in children's use of the tablet for typical activities related to units of measurement.